Nowe zjawiska w stosunkach handlowo-ekonomicznych Unii Europejskiej z Chińską Republiką Ludową - Puślecki, Zdzisław W. (Przegląd Politologiczny, 2018)
The topic of these considerations concerns the development of trade and economic relations between the European Union and the People’s Republic of China. Their purpose is to indicate new phenomena in these relations. Analysis has shown that mutual economic relations in the first decade of the 21st century expanded considerably on account of common interests. The economic crisis at the turn of the first decade of the 21st century inspired plans to stimulate the economies of both parties, and tighten mutual relations. On both sides there are the conditions and prerequisites to further develop and intensify broad economic cooperation. The Chinese competitive challenge, resulting from its dynamic development, is particularly topical and important for the prospects of the European Union’s global position.